An Unsuspected Case of Rocky Mountain Spotted Fever: A Lesson to Keep a Broad Differential - Sarah Barbina MD; Myra Quiroga MD; Chelsey Petz MD (SAGE Publishing, 2022)
Rocky Mountain spotted fever (RMSF), a tick-borne illness, can cause serious illness or death even in a healthy individual. Unfortunately, this illness can be difficult to diagnose as symptoms are nonspecific and oftentimes mimic benign viral illnesses. Delayed diagnosis can be detrimental as the timing of antibiotic administration is critical to prevent associated morbidity and mortality. A careful travel and social history can sometimes provide clues to make the diagnosis. Being aware of lesser-known objective findings such as hyponatremia, neurologic derangements, transaminitis, and thrombocytopenia may help raise suspicion for the disease. This is a case of a 72-year-old woman who presented with nonspecific symptoms and hyponatremia without known tick exposure. She was eventually diagnosed with RMSF. The timing of her presentation corresponded with a surge in COVID-19 infections throughout her area of residence, which further complicated her presentation and contributed to a delayed diagnosis.